Freiheit, Kontrolle und Verantwortlichkeit in der Gesellschaft. Moderne Biotechnologie als Lehrstück - Albrecht, Stephan (Hamburg University Press, 2006)
The responsibility of science is the starting point for intensive discussions. But who is responsible ty for what? This work is based on many years of research into the developments in modern biotechnology. The thorough analysis shows that responsibility is usually borne by the others. Political, legal, administrative and intra-scientific communication and action structures prevent or dilute responsibility to the point of inaccessibility. Stephan Albrecht uses numerous examples from the fields of medicine, agriculture, pharmacy and environmental technology to demonstrate that biotechnological progress is not evolutionary but political, man-made. However, a fundamental error in this progress is that it is not properly understood and negotiated in public, as a res publica. From a democratic point of view, the author proposes an institutional approach to the perception of responsibility in and for the sciences, which is oriented towards the specific challenges of technological innovation and at the same time builds on the best practices of political and civic decision-making.